Kalla yarning at Matagarup: Televised legitimation and the limits of heritage-making in the city - Kerr, Thor; Cox, Shaphan (University of Barcelona, 2017)
This paper is directed towards furthering understandings of popular television news reporting on Aboriginal solidarity gatherings at Matagarup on Heirisson Island, a state - registered Aboriginal Heritage Site in Perth, Western Australia. In doing so, it also seeks to identify the practical limits of heritage making in disrupting the legitimization of state action not recognizing such heritage claims. In 2012 and 2015, Aboriginal citizens gathering and camping at the heritage site were subject to police raids legitimized by popular media organizations reporting a breach of municipal bylaws prohibiting camping and fires on Heirisson Island. This paper examines a shift in popular television reporting over the three years towards acknowledging that Aboriginal people should be able to assemble, without police harassment, around a fire at the site. The most radical shift in reporting is observable in Nine News coverage of events. For this reason, eight televised items from Nine News in 2015 are analysed alongside Nine News reporting described in the authors’ previous study of reporting of events at Matagarup in 2012. The paper identifies and discusses the implications of two key dialogical processes in the news production: Firstly, a process of cross - cultural reading and shared understandings of fire as hearth, and secondly a process of reproducing a dominant discursive tradition locating home for Aboriginal people outside the city.